Analysis of sea surface temperature time series of the south-eastern North Atlantic - Borges; Hernández-Guerra, A.; Nykjaer, L. (International Journal of Remote Sensing, 2004)
The dominant periods in time series of sea surface temperature (SST) of the south-eastern North Atlantic are determined and related to atmospheric forcing and ocean dynamics. We analyse five-day composite images of a 10.5-year-long (from 10 July 1981 to 31 December 1991) time series of Advanced Very High Resolution Radiometer (AVHRR) onboard NOAA satellites. The dominant signal present in the whole region is the annual cycle. It explains 70% of the SST variance in the northern region and 40% in the southern. The pattern of the annual amplitudes is related to the seasonal cooling and warming cycle in the region. The second dominant period is a semi-annual frequency, estimated by means of periodograms of the residual time series with the annual cycle subtracted. This semi-annual frequency is responsible of making short springs and long autumns. The semi-annual frequency is present in 44% of the time series in the region, contrary to the generalized idea that a time series must always contain it. The geographical distribution of the semi-annual component of SST suggests that it is associated with the curl of the wind stress. The third dominant period is four years, found in three different areas: south of the Canary islands, off the Cape Verde islands and towards the northwest of Lanzarote Island. The main effect of this signal is to increase the maximum temperature every four years and to decrease the minimum temperature two years later. The 4-year signal does not seem to be associated with any atmospheric forcing field. The presence of a signal in the curl of the wind stress with periodicities of 25–30 days located south of the Canary Islands led us to conclude that the curl of the wind stress is important for the generation and shedding of eddies downstream these islands. 891 869 1,128 Q2 SCIE